Notes on the Chinese fauna of Ceratocanthinae (Coleoptera: Hybosoridae), with description of a new species of Eusphaeropeltis Gestro, 1898 - Jiang, Ri-Xin; Ballerio, Alberto; Guo, Liang; Wang, Shuo (Zootaxa, 2020)
The genus Eusphaeropeltis Gestro, 1898 (Coleoptera: Scarabaeoidea: Hybosoridae: Ceratocanthinae) is recorded for the first time from China and Eusphaeropeltis chenchaomingi Jiang, Ballerio, Guo & Wang, new species is described from Yunnan Province. Habitus and diagnostic features of the adult of the new species are described and illustrated. Details of Eusphaeropeltis male and female genitalia are illustrated for the first time. All known Chinese species of the subfamily Ceratocanthinae are listed and a distribution map is provided.